An investigation of the corrosion behavior of zinc-coated stainless steel orthodontic wires: the effect of physical vapor deposition method - Maryam Karandish; Negar Hajipour; Hanieh Yazdani; Mona Mahdavi; Mansour Rahsepar (BMC, 2024)
Abstract Background Releasing of metal ions might implicate in allergic reaction as a negative subsequent of the corrosion of Stainless Steel (SS304) orthodontic wires. The aim of this study was to evaluate the corrosion resistance of zinc-coated (Zn-coated) SS orthodontic wires. Methods Zinc coating was applied on SS wires by PVD method. Electrochemical impedance spectroscopy (EIS), Potentiodynamic polarization tests and Tafel analysis methods were used to predict the corrosion behavior of Zn-coated and uncoated SS wires in both neutral and acidic environments. Results The values of Ecorr ,icorr and Rct ,which were the electrochemical corrosion characteristics, reported better corrosion behavior of Zn-coated SS wires against uncoated ones in both artificial saliva and fluoride-containing environments. Experimental results of the Tafel plot analyses were consistent with that of electrochemical impedance spectroscopy analyses for both biological solutions. Conclusion Applying Zn coating on bare SS orthodontic wire by PVD method might increase the corrosion resistance of the underlying stainless-steel substrate.